Emergence of colistin-resistant Escherichia coli in poultry, house flies, and pond water in Mymensingh, Bangladesh - Sobur, Md Abdus; Ievy, Samina; Haque, Zobayda Farzana; Nahar, Ashrafun; Zaman, Sumaiya Binte; Rahman, Md Tanvir (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: Emergence of colistin-resistant Escherichia coli (CREC) has generated a sense of public alarm. The objective of this study was to detect the CREC and identification of the gene responsible for such resistance. Materials and Methods: A total of 150 samples comprising poultry cloacal swab, house flies (Musca domestica), and pond water were collected randomly from Mymensingh, Bangladesh and analyzed. Isolation and identification of E. coli were done based on culture and E. coli 16S rRNA gene-specific polymerase chain reaction (PCR). Phenotypic detection of CREC was done by disk diffusion method. Finally, colistin resistance genes were detected by PCR by using colistin resistant gene mcr3 specific primers. Results: Among the 150 samples, phenotypically 18.00% (n = 27/150) isolates were found as colistin resistant. By PCR, 8.00% of the E. coli isolates were found positive for the presence of mcr3 gene. Conclusions: Colistin resistant E. coli carrying mcr3 are detected in poultry, house flies and water that are of great public health concern. J. Adv. Vet. Anim. Res., 6(1): 50-53, March 2019